Antibodies as a source of anti-infective peptides: an update. (July 2015) - Magliani, Walter; Giovati, Laura; Ciociola, Tecla; Sperindè, Martina; Santinoli, Claudia; Conti, Giorgio; Conti, Stefania; Polonelli, Luciano
ABSTRACT : This review focuses on antibodies (Abs) and their function in immune protection, with particular emphasis on microbicidal Abs. Some aspects of Abs and Ab–drug conjugates as targeting therapeutic agents are also discussed. The main aim, however, is devoted to Ab-derived peptides modulating functions of the immune system and to the latest experimental evidence of Abs as a source of anti-infective and antitumor peptides derived from their complementarity determining regions and constant regions.